Evaluation of the effects of radiotherapy as a mode of treatment in management of advanced cancer cervix - BV, Rajeshwari (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Throughout world over 500000 new cases of invasive cancer cervix are detected each year and account for 15% of new cancer and 200000 deaths annually. In India more than 90,000 women suffer annually from cervical cancer and mortality of them report in advanced stage of disease. Methods: All cases were investigated with routine hematological and biochemical examination, x-ray chest, and ultrasonography of the abdomen and pelvis before starting radiotherapy treatment. All patients were examined and staged clinically according to the International Federation of gynaecologists and Oncologists (FIGO) staging system. Results: Majority of the patients 50% were in stage III B, followed by stage III A about 21% and 20% in stage IIB. During follow up, in study group maximum number of patients about 76% presented with skin changes like dryness, erythema, discoloration, diarrhea in 40%, obstructive uropathy in 16%, and in 4% developed vaginal stenosis. Conclusions: Today, malignancy is the challenge not only to the gynecologist, radiation oncologist but also to the patient. But because of newer technique and advances in medical field update in infrastructure gives to the specialist new dimension to treat the patient as well as raise of hopes to the patient.